The impact of integrated marketing communication towards customer’s brand awareness on food product / Nur Ain Azmy - Azmy, Nur Ain (Faculty of Business and Management, 2019)
The purpose of this research is to study the relationship of integrated marketing communication towards customer’s brand awareness on food product. Since there are too many product have arisen in the market especially in Fast Moving Consumer Goods (FMCG) that include of non-durable goods such as packaged foods, beverages, and other consumable so brand awareness become more important day by day. Besides that, there are varieties of integrated marketing communication that can impact towards customer’s brand awareness on food product. For this purpose 200 sets of questionnaires were distributed to anyone to the customers in Malaysia around Klang Valley shopping mall. Based on five (5) variables Advertising , Sales Promotion, Sponsorship and Electronic-Word of Mouth (E-WOM) and Brand Awareness. By considering brand awareness as a dependent variable in this research in order to find the relationship between IMC and brand awareness. Convenience sampling was the sampling method for this study. For this study, Saji brand has been chosen as subject matter. After the survey has been complete, the data was filled in the SPSS for analysis in order to get the result. The results show that Electronic-word of mouth (E-WOM) have the greatest impact towards customer’s brand awareness.